دراسة التآكل في بطانة برج التقطير الجوي في مصفاة بانياس - السيد, أحمد; سلامة, أحمد; فارس, حسان (Latakia University Journal -Engineering Sciences Series, 2019)
تم في هذا البحث إعداد تقييم لبيئة التآكل الداخلية لبرج التقطير الجوي، وذلك لإنجاز دراسة حول الحالة التآكلية لبطانة البرج في مصفاة بانياس النفطية. وقد تم إنجاز هذا العمل من خلال تجميع المعلومات حول عملية التقطير الجوي ومتغيراتها، ومن خلال تفتيش البرج تفتيشاً فنياً بعد ذلك. بدأت الدراسة بقياس النسب المئوية لمكونات النفط الخام الأكالة، ومن ثم أخذ عينات من نواتج التآكل من مختلف المناطق المتآكلة وتحليلها. بالإضافة إلى ذلك تم استخدام آلية الكوبونات لتحديد معدل التآكل في الأجزاء العلوية للبرج. تم تقسيم العمل إلى منطقتين تبعاً للتركيب المعدني للبطانة، وهما منطقة بطانة قبة البرج وبطانة جسم البرج. بينت الدراسة أن خليطة المونل400 تملك مقاومة جيدة للتآكل الناتج عن حمض كلور الهيدروجين في منطقة قبة البرج وذلك في شروط التشغيل الطبيعية. كما أن خليطة بطانة الجسم (الفولاذ المقاوم للصدأ من النوع S.ST.405) تملك مقاومة جيدة للتآكل في منطقة الجسم ماعدا المنطقة التي تكون فيها الحموض النفتينية شديدة الفاعلية التآكلية. In this research an evaluation of corrosion environment for atmospheric distillation column had been done, to realize a study of the corrosion situation of its lining in Banias Refinery Company. This work had been done by collecting the information about the distillation process and it's parameters and inspection the inside column technically after that. The study began with measuring the percentage of corrosive of crude oil, then take specimens of corrosion products from different corroded areas and analyze them. Besides of that, two types of coupons were been used to determine corrosion rates in the column overhead parts. The work was divided in to two areas according to the lining metallic composition, the column overhead lining and body lining. The results have been showed that monel 400 alloy has good resistance against the corrosion that caused by HCl at column overhead parts in conditions work normal. S.St.405 alloy also has good resistance for corrosion in column body region except the region that the naphthenic acids is very effective.